Actin fenestrae amplify the membrane response to hypertonic stress in osmosensory neurons - Anzala Murtaz; Charles W. Bourque (iScience, 2025)
Summary: Osmosensory neurons detect hypertonic stress when ΔN-TRPV1 channels are activated through a push force delivered by microtubules during cell shrinking, and this process requires an essential yet unknown contribution from actin filaments. Here, we show that the actin cortex of these neurons feature fenestrations that allow for the formation of pits that magnify the osmotically induced displacement of the plasma membrane compared to that expected from uniform shrinking. Furthermore, we found that many N-terminal variant of the transient receptor potential vanilloid 1 (ΔN-TRPV1) channels attached to microtubules are aligned with fenestrae and such sites undergo greater hypertonicity-induced displacement than predicted by geometrically uniform cell shrinking. These results indicate that actin filaments contribute to the establishment of nanoscale architecture at sites which may optimize osmosensory transduction.